4n-12=12n-4

Simple and best practice solution for 4n-12=12n-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-12=12n-4 equation:


Simplifying
4n + -12 = 12n + -4

Reorder the terms:
-12 + 4n = 12n + -4

Reorder the terms:
-12 + 4n = -4 + 12n

Solving
-12 + 4n = -4 + 12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-12n' to each side of the equation.
-12 + 4n + -12n = -4 + 12n + -12n

Combine like terms: 4n + -12n = -8n
-12 + -8n = -4 + 12n + -12n

Combine like terms: 12n + -12n = 0
-12 + -8n = -4 + 0
-12 + -8n = -4

Add '12' to each side of the equation.
-12 + 12 + -8n = -4 + 12

Combine like terms: -12 + 12 = 0
0 + -8n = -4 + 12
-8n = -4 + 12

Combine like terms: -4 + 12 = 8
-8n = 8

Divide each side by '-8'.
n = -1

Simplifying
n = -1

See similar equations:

| 11n=10n+16 | | 2x+58=6x-10 | | -5(3x+4)=4x+16-7x | | 0.3x-0.5x+3=-4 | | -4x-5x= | | 9n-34=6n+5 | | m+(-5)=19 | | 5(x+4)=6(3x-2) | | 4y+xy=11 | | .75a+14=8 | | 2(1-2b)+2(1+5b)=-9+6b | | (x^4)+(41x^2)+400=0 | | 6p+(p-4)=4p | | 264-3x=42x+19 | | -36x^4+25x^3-4= | | h+(-9)=-9 | | (x^4)+(4x^2)+400=0 | | 15t+9=5t+9 | | 5b-12=14 | | 9(x-4)=72 | | -10y-7=6y+9 | | d-15=44 | | -441=4(-8n-4) | | 2(8x+2)=3(2x-7) | | 5x+2x=6x-2 | | 5x-6(3x+4)=9(x-6)+3 | | -9x+4x+15-10x= | | 7u^2-48u-7=0 | | 0.02-0.02(x+2)=-0.04(2-x) | | 6x+6=4x+2 | | 4-(3.5x+2)=x-7 | | 10y-7-6y+9= |

Equations solver categories